Development of android-based learning media applications on mole concept topics for high school students - Istiva Depiyahani; Fajriah Azra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to develop a product in the form of an Android-based learning media application based on the mole concept material for class X SMA/MA that is valid and practical. The study uses the Plomp development research model, which consists of three steps: preliminary research, prototyping phase, and assessment phase. This research is limited to the prototyping phase for the practicality stage of the small group evaluation. Three chemistry lecturers carried out the product validity test at the Faculty of Mathematics and Natural Sciences, Padang State University, two Al-istiqamah High School chemistry teachers as material experts, and two lecturers of informatics engineering at Padang State University as media experts. Fifteen students and two chemistry teachers carried out the practicality test. The validity data analysis technique uses Aiken's V index. The validity test results showed that the Android-based learning media application developed belongs to the valid category with an average V value of 0.86 for material experts and an average V value of 0.93 for media experts. The practicality data analysis technique uses a percentage formula. The results of the practicality test in small groups are classified as